Synthesis and mesomorphism of tetrafluoro substituted 4-cyano oligophenyls. Issue 11 (2nd September 2019) - Herman, Jakub; Dmochowska, Ewelina; Pytlarczyk, Marta; Harmata, Piotr
ABSTRACT: The synthesis and characterisation of new liquid crystal (LC) compounds based on terphenyl core are described. New family of dielectrically positive compounds presents alternative molecular approach to the conventional LC design. Correlations between molecular structure and mesomorphic properties for compounds being cyano terminated analogues as well as other known from the literature have been drawn. Compounds are characterised by 1 H NMR spectroscopy and mass spectrometry (electron ionisation) analysis. They show monotropic nematic behaviour in broad temperature range, confirmed by a polarising thermomicroscopy, differential scanning calorimetry. Detailed synthetic procedures are attached. Synthesised compounds stand as promising components of medium to highly birefringent liquid crystalline mixtures. Graphical abstract: